2017
DOI: 10.1089/cyber.2017.0183
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effects of Playing Exergames: A Systematic Review

Abstract: Successful exergames should lead players not only to achieve enough level of energy expenditure but also to engage in the play itself. The aim of this study is to review studies that explored the psychological effects of playing exergames, from the viewpoint of player engagement. Peer-reviewed journal articles in English collected via database search (Science Direct, Web of Science, ACM Digital Library) from 2011 to 2015 were considered, and 45 experimental studies were selected out of 911 studies. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 96 publications
3
61
0
3
Order By: Relevance
“…Exergaming seems to benefit motivation, which might increase the potential to foster cognitive performance in children with ADHD. It has, for example, been shown that exergaming increases motivation and engagement in physical activity, eliciting motivational gains, as well as flow, immersion, and enjoyment . However, since the intervention was compared to a wait‐list control group, motivation has not been examined in the current study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Exergaming seems to benefit motivation, which might increase the potential to foster cognitive performance in children with ADHD. It has, for example, been shown that exergaming increases motivation and engagement in physical activity, eliciting motivational gains, as well as flow, immersion, and enjoyment . However, since the intervention was compared to a wait‐list control group, motivation has not been examined in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…It has, for example, been shown that exergaming increases motivation and engagement in physical activity, eliciting motivational gains, as well as flow, immersion, and enjoyment. 61,62 However, since the intervention was compared to a wait-list control group, motivation has not been examined in the current study. Therefore, further research is warranted to investigate whether physically and cognitively challenging exergaming is equally beneficial to either cognitive or physical exercise training regarding commitment, motivation as well as outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, it improves levels of physical activity and achieves enough level of energy expenditure, reducing the boredom of repeated physical movements through increasing enjoyment and improving the adherence. [16][17][18][19][20][21][22] Therefore, it is believed that exergaming may be a positive strategy to promote changes in sedentary behavior of children and adolescents with overweight or obesity. 23 Studies involving exergames have grown significantly in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Systematic reviews of the effects of exergames have focused on the physiological or health aspects of children and adolescents [28][29][30][31][32][33][34][35][36][37] in a specific population. 20 However, with regard to the psychological benefits for children and adolescents with overweight or obesity, research is still scarce. In this sense, it is important to summarize and analyze what these studies indicate about the psychological effects of exergaming for this population.…”
Section: Introductionmentioning
confidence: 99%
“…So far, studies in the field of exergaming have investigated various effects of commercially available and specifically developed exergames in different target population such as children, adolescents, seniors or patients. Results deliver indications for effects on the cognitive (e.g., executive functions, attention and visual-spatial skills) (Staiano and Calvert, 2011;Best, 2015;Benzing et al, 2016;Mura et al, 2017;Stojan and Voelcker-Rehage, 2019;Xiong et al, 2019), physical (e.g., energy expenditure, heart rate, and physical activity) (Staiano and Calvert, 2011;Sween et al, 2014;Best, 2015;Kari, 2017) and mental (e.g., social interaction, self-esteem, motivation, and mood) (Staiano and Calvert, 2011;Li et al, 2016;Joronen et al, 2017;Lee et al, 2017;Byrne and Kim, 2019) level. Generally, exergames are very well known for their playful combination of physically and cognitively challenging tasks and thus provide dual domain training, which indicates to have greater effects compared to traditional training approaches (Schättin et al, 2016;Ballesteros et al, 2018;Egger et al, 2019;Stojan and Voelcker-Rehage, 2019).…”
Section: Evidence In Exergame Trainingmentioning
confidence: 99%